Patient-nurse ratio as an index related to healthcare-associated infections: a surveillance study - Daniela de la Rosa-Zamboni; Miroslava I. Carrasco-González; Norma de Blas-Barrientos; María L. Flores-Constatino; Erika Flores-Zamora; Martha Camacho-Pérez; Itzel G. Neri-Saldaña; Ana C. Guerrero-Díaz (Permanyer, 2023)
Background: Healthcare-associated infections (HCAIs) are a hospital problem with a prevalence of approximately 5% in Mexico. HCAIs have been related to the patient-nurse ratio (PNR). This study aimed to analyze the association between PNR and HCAI in a tertiary-level pediatric hospital. Methods: We conducted a descriptive and prospective study at a tertiary-level pediatric hospital in Mexico. Nursing attendance and HCAIs records were documented from July 2017 to December 2018. PNR was calculated using nurse staffing records and patient census. Results: We obtained 63,114 staff attendance data from five hospital departments for the morning, evening, and night shifts. PNR > 2:1 was associated with a 54% (95% confidence interval (CI) 42-167%; p < 0.001) increased risk (odds ratio (OR)) for HCAIs, adjusted by shift staff, special conditions, and surveillance periods. The HCAIs more associated with PNR were urinary tract infections (OR 1.83; 95%CI 1.34-2.46), procedure-related pneumonia (OR 2.08; 95%CI 1.41-3.07), and varicella (OR 2.33; 95%CI 1.08-5.03). Conclusions: A high number of patients per nurse increased the probability of various types of HCAI. PNR needs to be established the HCAI guidelines and policies, as regulating the number of patients per nurse can prevent HCAIs and their complications.